From Sunspots to Black Holes: Singular dynamics in macroeconomic models : model with endogenous markups - Brito, Paulo (2008)
We develop a simple Ramsey model with numerous Cournotian industries where entry generates an endogenous markup. The model produces two different regimes: a monopoly and an oligopoly one. We provide a rigorous study of non-smooth dynamics and we also analyse the global dynamics of the model, demonstrating the model exhibits robust heteroclinic orbits, either of the smooth or the non-smooth type. Similar economies may be in any of these regimes and they may change regime along its convergence path. Fixed costs and elasticities of demand, play a crucial role and changing their values may alter the dynamics in a radical way, either by inducing a discontinuous transition or a discontinuous hysteresis.